2023
DOI: 10.3390/pharmaceutics15092283
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Carvedilol Oral Liquid Formulation for Paediatric Use

Blanca Chiclana-Rodríguez,
Encarnacion Garcia-Montoya,
Khadija Rouaz-El Hajoui
et al.

Abstract: Carvedilol (CARV) is an ‘off-label’ β-blocker drug to treat cardiovascular diseases in children. Since CARV is nearly insoluble in water, only CARV solid forms are commercialized. Usually, CARV tablets are manipulated to prepare an extemporaneous liquid formulation for children in hospitals. We studied CARV to improve its aqueous solubility and develop an oral solution. In this study, we assessed the solubility and preliminary stability of CARV in different pH media. Using malic acid as a solubility enhancer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 28 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…The initial C8_P2 pH value was 2.47, and initial data on the C8_P2 appearance indicated that it was a clear, translucent solution without any undissolved particles. C8_P2 exhibited identical physicochemical characteristics to those of the reference CARV solution on which it is based [ 10 ]. pH results for C8_P2 were highly stable over time with a range of variation ± 0.03.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial C8_P2 pH value was 2.47, and initial data on the C8_P2 appearance indicated that it was a clear, translucent solution without any undissolved particles. C8_P2 exhibited identical physicochemical characteristics to those of the reference CARV solution on which it is based [ 10 ]. pH results for C8_P2 were highly stable over time with a range of variation ± 0.03.…”
Section: Resultsmentioning
confidence: 99%
“…CARV formulations we studied herein were based on the optimized CARV formulation described in our last research [ 10 ]. The characteristics of the CARV formulation we developed are presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations